Hot forming tribology : galling of tools and associated problems - Pelcastre, Leonardo (Luleå tekniska universitet, Maskinelement, 2011)
In recent years, the use of ultra high-strength steels (UHSS) as structural reinforcements and in energy-absorbing systems in automobiles has increased rapidly; mainly in view of their favourable strength to weight ratios. However, due to their high strength, the formability of UHSS is poor, thus complex-shaped UHSS components are invariably produced through hot-metal forming processes. The use of hot stamping or press hardening, which was developed during the 1970’s in northern Sweden, has become increasingly popular for the production of ultra high strength steels. In hot stamping, different tribological problems arise when the tool and work-piece interact during the forming process at elevated temperatures. Wear and surface damage of forming tools can be detrimental to the quality of the final product and these can also have an adverse impact on the process economy due to frequent maintenance or replacement of tools. In this work, a literature review pertaining to tribology of hot sheet metal forming has been carried out. This review has revealed that the awareness of tribology and its application in metal forming processes at high temperature has increased in the recent years. A considerable amount of work has been done to enhance the understanding of the response of different materials and parameters involved and also to improve the process itself. However, despite these developments, there exist major gaps in knowledge pertaining to the occurrence of friction and wear in hot sheet metal forming. Extensive experimental studies have thus been undertaken to bridge some of the knowledge gaps related to tool wear and failure mechanisms in the hot stamping process. These studies have involved both the systematic analysis of actual worn tools as well as parametric tribological investigations in the laboratory. The analysis of worn tools showed that friction is a crucial parameter in their operating life. It was observed that severe mechanical stresses are generated due to high friction during the work-piece/tool ...